Швидкі іон-акустичні солітонні хвилі в гарячій плазмі від’ємно заряджених іонів з двотемпературними неізотермічними електронами - Chattopadhyay, S. (Publishing house "Academperiodika", 2025)
Using the Sagdeev pseudo-potential formalism, the study of large-amplitude ion-acoustic compressive fast-mode solitons and fast-mode phase plane trajectories has been performed for a model plasma composed of warm positive and negative ions, warm positrons and twotemperature nonisothermal electrons. The critical phase velocity (Vc) is first obtained analytically by solving the dispersion relation under various physical conditions. Based on this analysis, the fast-mode phase velocity is subsequently identified as the velocity that not only exceeds the critical value, but also satisfies the criteria for the existence of solitary wave solutions, including all required boundary conditions. It is now observed from our model that the fast-mode phase velocity (VF) is found after crossing a certain limit of critical phase velocity (Vc) for some chosen set of plasma parameters and finally the large-amplitude fast-mode compressive solitons and fast-mode phase plane trajectories of bounded periodic solutions are found under the variation of the stream velocities of positive and negative ions, the phase velocity, the temperatures of both ions and the concentration of negative ions.